Pengaruh Budaya Organisasi Dan Kepuasan Kerja Terhadap Kinerja Karyawan Dengan Komitmen Organisasional Sebagai Variabel Interverning Pada PT Growth Industri Sumatera - Tjendana, Martinus (Lembaga Riset Ilmiah, 2022)
Employee performance is the most important factor in improving the company's progress, therefore every company should pay attention to matters relating to employee performance where this research was carried out by paying attention to organizational culture and job satisfaction on employee performance with organizational commitment as an intervening factor. By taking a sample of 152 employees at PT Growth Industry Sumatra and analyzing it using SEM. The results show that organizational culture and job satisfaction, as well as organizational commitment, have a simultaneous and partial effect on organizational commitment. And Organizational Commitment affects employee performance